Estado, atores predominantes e coaliz\~oes para o desenvolvimento: Brasil e Argentina em perspectiva comparada - Flavio Gaitán; Renato Raul Boschi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper aims to analyze the role of government coalitions in the formulation and implementation of a socioeconomic development model. It is a qualitative research that focuses on the extent to which the formation of coalitions to support a developmental platform is efficient in formulating and implementing sustainable public policies in the medium and long term in order to shape a national development agenda. The central hypothesis is that the development process has a direct relationship with the institutional dimension, in particular the role of the State, of government coalitions, of various public institutions (especially those that tend to coordinate interests' between the public and private sectors) and strategic actors profiles in the formulation and implementation of policies. From the interactions established between State, institutions and strategic players different styles or patterns of development are configured. "Developmental coalitions" is defined as the convergent action of different actors involved in any dynamic of growth and development (Tanaka, 2012). The "strategic actor" category includes business, organized labor and public bureaucracy. However, we focus on business and labor vis-à-vis the political field, which represents the space of articulation of interests of the different strategic actors. The methodological approach consists in the evaluation, based on stylized facts, of the turning points of the economic models (neoliberal and post-neoliberal) and the analysis of positions (statements, actions, exclusions) of strategic elites.
Keywords: O21; O38; O43; 330; state; coalitions; elites; Argentina; Brazil; development